2017
DOI: 10.1007/s10961-017-9604-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the productivity of technology transfer offices: an analysis of the relevance of aspiration performance and portfolio complexity

Abstract: Paper published in the Journal of Technology Transfer. Please cite as:Lafuente, E., Berbegal-Mirabent, J. (2017). Assessing the productivity of technology transfer offices: an analysis of the relevance of aspiration performance and portfolio complexity. . We analyze the productivity of Spanish TTOs during 2006-2011 by computing total factor productivity models rooted in non-parametric techniques, namely the Malmquist index. The results confirm that technology transfer productivity is affected by changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 53 publications
(103 reference statements)
3
40
0
Order By: Relevance
“…It was observed that the efficiency of most departments improved within the period under review, even though this improvement could not be explained, given factors such as the number of faculties with PhDs and university location, among other things. The result also follows that of Lafuente and Berbegal-Mirabent (2019), who suggested, using the Malmquist index, that efficiency can be boosted by creating benchmarking of their own productivity levels within the market in comparison to those of other Spanish universities within a five-year period. In order to compare the influence of local and international innovation systems on the overall efficiency of the Chinese innovation system, Qin and Du (2017) utilized direct investments from foreign nations and cooperation between industry and universities as key factors to point to the invention of technology, as well as its commercialization, as input and output.…”
Section: Number Of Equity Spin-offssupporting
confidence: 82%
“…It was observed that the efficiency of most departments improved within the period under review, even though this improvement could not be explained, given factors such as the number of faculties with PhDs and university location, among other things. The result also follows that of Lafuente and Berbegal-Mirabent (2019), who suggested, using the Malmquist index, that efficiency can be boosted by creating benchmarking of their own productivity levels within the market in comparison to those of other Spanish universities within a five-year period. In order to compare the influence of local and international innovation systems on the overall efficiency of the Chinese innovation system, Qin and Du (2017) utilized direct investments from foreign nations and cooperation between industry and universities as key factors to point to the invention of technology, as well as its commercialization, as input and output.…”
Section: Number Of Equity Spin-offssupporting
confidence: 82%
“…Face-to-face semi-structured interviews were conducted with the different industrial liaison in Sweden and Ireland. Five (5) to six (6) people were interviewed from each university in Sweden and industrial liaison office representatives were interviewed in each university in Ireland. Data gathered from these universities were subjective to qualitative analysis.…”
Section: Barriers Of University Technology Transfer (Utt)mentioning
confidence: 99%
“…The United Nations Industrial Development Organization (UNIDO) [4] defined technology transfer as the process by which a collected entity (i.e., an act of manufacturing a product, application of a process, execution of service) is conveyed, partially or wholly, from one party to another. Generally, technology transfer is used as a tool to disseminate and commercialize intellectual properties, converting it to products for public use [5,6]. While their usual medium is commercialization, community extension services are becoming increasingly popular platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while older TTOs positively contribute to the performance of French TTOs in the short run, young TTOs with hospitals seem to contribute negatively to the efficiency of the entire system (Curi, Daraio, & Llerena, 2015). Lafuente and Berbegal-Mirabent (2017) have analysed the productivity of Spanish TTOs during 2006-2011 by computing total factor productivity models rooted in non-parametric techniques, namely, the Malmquist index (Lafuente & Berbegal-Mirabent, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%